Anomalia gravimétrica residual da Bacia de Barreirinhas obtida a partir da modelagem Crustal GEMMA - RIBEIRO FILHO, Nelson de Lima (2018)
In this work, a regional-residual separation procedure is presented for the interpretation of gravity data in sedimentary basins through the crustal modeling. A modeling was performed from available data of the GEMMA crustal model, which informs the top and bottom depth values of the crust and the distribution of density vertically and horizontally discretized in layers and associated with geological provinces. The gravity anomaly of the modeled crust was evaluated at the same observation points of available gravity data. The area corresponding to the continental portion of the Barreirinhas Basin was selected. The gravity data used come from four different sources: 1) public ground gravity data from the Exploration and Production Database (BDEP / ANP); 2) of the Geodetic Database (IBGE); 3) gravity data acquired in field survey; 4) and satellite gravity data from ESA space missions, available on the ICGEM online platform. Once the gravity signal is computed due to the Moho of the selected region, we assume that the residual signal is obtained by the difference between the observed signals and the calculated regional. Additionally, other regionalresidual separation methodologies were used for comparison purposes, specifically the Spectral Analysis and the Robust Polynomial Fitting. These two techniques were not effective delineating the gravity signal for the Barreirinhas Basin. However, the presented procedure based on crustal modeling proved effective to select the residual signal presumed to the Barreirinhas Basin. This procedure can be applied for the interpretation of residual anomalies in any sedimentary basins.